Management of Y-Site Incompatibility of Intravenous Medication: A Scoping Review - Suci Hanifah; Patrick Ball; Ross A Kennedy (Indonesian Journal of Pharmacy, 2022)
Patients in intensive care units have a critical problem with Intravenous (IC) drug administration. The effort to decrease incompatibility or manage the incompatibility risks is paramount significant to reduce morbidity and mortality. This review collates all published studies about kinds of approaches to prevent or solve y-site incompatibility, evaluate the effectiveness of those approaches, and provide the recommendation. A scoping review was conducted in PUBMED in a time frame 1 Januari 2010- 28 February 2021. All type studies of randomised controlled trials, observational studies, before and after studies, also review articled were considered to include. We identified 944 studies; of these, 78 met the inclusion criteria, but 44 were excluded. A total 34 articles were included in the analyses.  Six articles reported protocol, two-dimensional chart, database, or pH colour code to provide information of incompatibilities. Two-dimensional chart and pH code were comparable with a gold standard. Specific protocol markedly reduced the incompatibility event. Normal saline (NS) flushing effectively prolonged patency and reduced the incompatibility rate. NS was preferred over heparin associated with thrombocytopenia. In-line filtration has been proved to reduce particulate matter, as well as the precipitation, resulted from incompatibility. The filter also reduced inflammation, infection, and complication appreciably. Four studies used more than three lumen catheters which successfully decrease the number of precipitation and incompatibility events. Therefore, separating incompatible drugs using multi-lumens according to the chart should be preferred. However, when co-administration is inevitable, flushing or filter is needed.